Theoretical Investigation of Steric and Electronic Effects of meso-Phenyl on Co-Porphyrin Catalyzed Activation of Dioxygen - Liu, Nian; Wei, Deng; Jiang, Guo-Fang; Guo, Can-Cheng (Asian Journal of Chemistry, 2014)
The molecule oxygen (O2) activated on cobalt tetraphenylporphyrin (CoTPP) to form the peroxide species CoTPPO2, which is the key intermediate in the behavior of metalloporphyrin catalyzed hydrocarbon oxidation, was simulated by the quantum chemical calculations. The effect of the meso-phenyl ring on the formation of the peroxide species CoTPPO2 was investigated for the first time. The molecular geometry studies indicated that the meso-phenyl ring rotated with the molecule oxygen coordinated with CoTPP. Further nature atomic charge and nature bond orbital analysis supported that the steric changing of the meso-phenyl has a positive effect on the electron transport between CoTPP and O2 to from the peroxide intermediate.